Intertextualidades em ambientes digitais - Costa, Dálete Castro Braga (2024)
From the perspective of Text Linguistics, this paper ponders the processes of intertextuality and expands on its modes of expression in native digital texts, with a view to technodiscursivity. In other words, this research provides an explanation of how technological resources promote relationality between texts through social networks, with the technological tools we use in our daily lives today. To this end, with regard to intertextuality, we base our work on Genette (2010); Piégay-Gros (2010); Carvalho (2018) and Cavalcante (2021); as for technodiscursivity, we draw on Paveau (2021); Cavalcante (2022) and Muniz-Lima (2022). We assume, along with Cavalcante et al. (2022), that technodiscursivity is an assumption that acts of language unite with the technological resources of the machine, establishing a human-machine interaction. We agree with Bakhtinian dialogism that texts are always in dialog with other texts, which is likely to occur in productions circulating on the internet, which have particular properties and require attention from the Language Sciences. Text Linguistics, specifically, is interested in the marking of these dialogues, called intertextuality. Based on Carvalho (2018), we assume that the phenomenon of intertextuality is subdivided into strict (when a specific text is mentioned) and broad (when a set of non-specific texts shared in a given society is mentioned). As for methodology, this research is hypothetical-deductive in nature and arose from the observation of gaps in previous research regarding the study of intertextuality in technodiscursivity. In order to achieve our general objective, we took the following steps: i) we analyzed how mentions to other texts occur in technotexts in order to describe them; and ii) we considered the intertextual processes crystallized in Textual Linguistics in order to give them a post-dualist look and analysis of the categorical framework already established in TL studies. This paper aims to understand how intertextuality works in technodiscursivity in order to describe how intertextual processes occur in a digital environment. We therefore needed to look at the resources provided by the internet media and selected posts from Instagram and Twitter/X that have their own resources such as handles, hashtags, links, retweets, external shares, and search tracking, among others. In this research, we highlight some results: 1) the reference of a specific text or a set of texts within digital enunciative events can occur in two ways: the first is technical, which concerns mentions through the use of resources provided by the machine; the second is not, as it concerns mentions through multisemiotic utterances. Taking into account the relationality of technotexts, 2) the process of mention (PIÉGAY-GROS, 2010) must be part of strict intertextuality, because it is a phenomenon of mention that is distinct from allusions and, in technotexts, we realize that this mention usually occurs through a clickable linguistic segment. In addition, we believe that 3) broad allusions can permeate all strict intertextualities; 4) the intertextual process of strict allusion makes use of a “set of network data”; finally, 5) the resource of “sharing” promotes processes of transposition.